Evaluasi Dalam Pembelajaran Bahasa Arab di Sekolah Dasar Tahfidzul Qur’an Terpadu An-Najah Martapura - Husna, Nurul (Anterior Jurnal, 2016)
The aim of this study is to know how the evaluation of learning Arabic and the follow-up done by teachers in elementary school of Integrated Tahfidzul Qur’an An-Najah Martapura and what are the factors that affect the implementation of the evaluation of learning Arabic in elementary school of Integrated Tahfidzul Qur’an An-Najah Martapura. The analysis of this study used verification analysis, that is by providing explanations of existing data based on objectivity and honesty of statements obtained in order to test the truth of the theory which has been described previously. The results of this study showed that the evaluation of learning Arabic and the follow-up done by teachers in the elementary school of Integrated Tahfidzul Qur’an An-Najah Martapura is in a good category. The factors that affect the implementation of the evaluation of learning Arabic in elementary school of Integrated Tahfidzul Qur’an An-Najah Martapura is the background of teachers is appropriate to their subjects, the teaching experience is very supportive, the activities of teachers to improve teacher skills are good enough, the number of classes which is handled and the number of subjects taught also support and the motivation of the principal has been good.